2021
DOI: 10.1155/2021/6518221
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Glucagon-Like Peptide-1 Receptor Agonists and Dipeptydilpeptidase-4 Inhibitors on Blood Pressure and Cardiovascular Complications in Diabetes

Abstract: Glucagon-like peptide-1 receptor (GLP-1R) agonists are a class of newly introduced antidiabetic medications that potentially lower blood glucose by several molecular pathways. DPP-4 inhibitors are the other type of novel antidiabetic medications which act by preventing GLP-1 inactivation and thereby increasing the activity levels of GLP-1, leading to more glucose-induced insulin release from islet β-cells and suppression of glucagon release. Most patients with diabetes have concurrent hypertension and cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 116 publications
0
7
0
Order By: Relevance
“…Since their first approval in 2005, glucagon‐like peptide‐1 receptor agonists (GLP‐1 RAs) have been widely prescribed for type 2 diabetes mellitus (T2DM) and obesity 1 . Their promising results in glycaemic control and weight loss, together with a low risk of inducing hypoglycaemia and a favourable cardiovascular and renal safety profile, have made them desirable therapies for the treatment of T2DM as well as its comorbidities and complications 2–8 . Since their introduction, several different formulations of these antidiabetic agents have been brought to market; to date, seven injectable analogues (twice‐daily exenatide immediate‐release, once‐weekly exenatide extended‐release, once‐daily liraglutide, once‐daily lixisenatide, once‐weekly albiglutide [currently off‐market due to a decline in sales], once‐weekly dulaglutide and once‐weekly semaglutide) and one orally‐administered analogue (once‐daily semaglutide) have been approved by the Food and Drug Administration (FDA) 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since their first approval in 2005, glucagon‐like peptide‐1 receptor agonists (GLP‐1 RAs) have been widely prescribed for type 2 diabetes mellitus (T2DM) and obesity 1 . Their promising results in glycaemic control and weight loss, together with a low risk of inducing hypoglycaemia and a favourable cardiovascular and renal safety profile, have made them desirable therapies for the treatment of T2DM as well as its comorbidities and complications 2–8 . Since their introduction, several different formulations of these antidiabetic agents have been brought to market; to date, seven injectable analogues (twice‐daily exenatide immediate‐release, once‐weekly exenatide extended‐release, once‐daily liraglutide, once‐daily lixisenatide, once‐weekly albiglutide [currently off‐market due to a decline in sales], once‐weekly dulaglutide and once‐weekly semaglutide) and one orally‐administered analogue (once‐daily semaglutide) have been approved by the Food and Drug Administration (FDA) 9 .…”
Section: Introductionmentioning
confidence: 99%
“…1 Their promising results in glycaemic control and weight loss, together with a low risk of inducing hypoglycaemia and a favourable cardiovascular and renal safety profile, have made them desirable therapies for the treatment of T2DM as well as its comorbidities and complications. [2][3][4][5][6][7][8] Since their introduction, several different formulations of these antidiabetic agents have been brought to market; to date, seven injectable analogues (twicedaily exenatide immediate-release, once-weekly exenatide extendedrelease, once-daily liraglutide, once-daily lixisenatide, once-weekly albiglutide [currently off-market due to a decline in sales], onceweekly dulaglutide and once-weekly semaglutide) and one orallyadministered analogue (once-daily semaglutide) have been approved by the Food and Drug Administration (FDA). 9 Besides GLP-1 receptor as their putative target, numerous molecular targets have been identified for GLP-1 RAs, [10][11][12][13][14][15][16][17][18][19] which justifies their potential for wider medical applications.…”
mentioning
confidence: 99%
“…DPP-IV inhibitors or gliptins, a new family of hypoglycemic medicines, increase the production of GLP-1 by inhibiting its deactivation and enhancing its action. As a result, glucagon release is reduced, and more glucose-induced insulin is secreted by islet cells [ 57 ]. DPP-IV inhibition possibly leads to the formation of Akt/endothelial NO synthase (eNOS), resulting in increased formation of NO and enhancement of fibroblast growth factor 2 (FGF-2)/early growth response protein 1 (EGR-1)/vascular endothelial growth factor A (VEGF-A) signaling [ 58 ].…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Endothelial cells play a key role in BP control. GLP-1RAs stimulate acetylcholine-induced vasodilation and promote nitric oxide release, thus reducing vascular tone with benefits to both systolic and diastolic BP [44]. A recent study demonstrated that acute pharmacological stimulation of GLP-1R increases eGFR by promoting diuresis and natriuresis through the inhibition of the major renal proximal tubule sodium reabsorption pathway.…”
Section: Glp-1ras and Reduction In Cardiovascular Riskmentioning
confidence: 99%